Estudo teórico e experimental das pressões em tremonhas cônicas e piramidais de silos metálicos esbeltos - Vieira, Luciano Henrique de Souza (2009)
The hopper structure is still an area of great uncertainties regarding the product flow and the acting pressures. Its behavior during loading and downloading products is little known. With the eccentricity of the discharge hopper, the uncertainties only increase, resulting, at times, in insecure or anti economic projects. This study design was based on the AS 3774:1996 (Australian) and on the EN 1991-4:2006 (European) norms. The results obtained were compared to an experimental study that tests two hopper models in reduced scale, being one a metallic pyramidal hopper, with 33% of eccentricity; the other, conic, with 55% of eccentricity. For the tests, sand was used as a granular product and pressures charges were applied by using a hydraulic press, simulating different height/diameter ratios. From the research findings, it was concluded that both norms presented satisfactory calculation methods to determine the pressures in pyramidal hoppers. The application of the method 2 of EN 1991-4:2006 provided pressures values superior to the ones found during the tests, leading to a more conservative dimensioning of its structure. The norm EN 1991-4:2006 offers better results for the conic hopper. However, the AS 3774:1996 can also be used to determine the pressures in eccentric conic hoppers.